Assessing Risk in North Dakota Juvenile Probation: A Preliminary Examination of the Predictive Validity of the Youth Assessment and Screening Instrument - Matz, Adam K. (Crime & delinquency, 2021)
This exploratory research examines the predictive accuracy of the Youth Assessment and Screening Instrument adopted by the North Dakota Juvenile Court through a retrospective review of assessment and court records. While studies of YASI from New York, Virginia, and Canada provide some confidence in the instrument’s predictive validity, questions remain concerning its accuracy among female and other specialized populations. This study finds a moderate effect for the instrument’s predictive accuracy in relation to general reoffending from a random sample of juvenile probationers (AUC = 0.66, p = .002, 95% CI [0.56, 0.75], N = 139), but results were notably weaker for females compared to males. Further research is needed on its accuracy among African American and Native American youth.